A REVIEW LITERATURE EMPLOYEE PERFORMANCE MODE: LOCUS OF CONTROL, MOTIVATION, JOB SATISFACTION AND COMPENSATION - Desi Permata Sari; Nandan lima Krisna (Dinasti Publisher, 2021)
This study aims to determine the model of employee performance that is influenced by locus of control, motivation and job satisfaction and compensation. The method of writing scientific articles is to use qualitative methods and library research. The results of this literature article are: locus of control has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, and compensation has a positive and significant effect on employees.